Modern practices of social service and charity of Penza diocese (1991–2024) - A.B. Shigurova (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. The article examines the issue of the formation and current state of the social service of Penza diocese of the Russian Orthodox Church in the period from 1991 to 2024. Particular attention is paid to the formation of diocesan social service department and the currently implemented practices of church charity. The relevance of the study is seen in the fact that the recent history and current state of church social service, especially in Penza diocese, are not sufficiently covered in science. The purpose of the work is to study the practices of social work and charity currently implemented by the Penza diocese, their directions and forms. Materials and methods. The implementation of research tasks was achieved based on the use of materials from the official publications of the Penza dio-cese “Penza Diocesan Bulletin” (2010–2024), “Penza Orthodox Interlocutor” (2004–2024), official websites of Penza diocese, the department of social service and charity of Penza di-ocese, as well as materials from the archives of the department of social service and charity of Penza diocese. The methods of historical analysis and content analysis were chosen as the main methods. Results. The work identifies the main directions and forms of social work practices and charitable activities of Penza diocese in 1991–2024, and examines the recent history of the diocesan department of social service and charity. Conclusions. Mod-ern practices of social service and charity of Penza diocese are implemented within the framework of the following areas of work: volunteerism, protection of the family, mother-hood and childhood, abortion prevention, hospital ministry, assistance to people with disa-bilities, the elderly, the homeless and people in difficult life situations, prevention of alco-holism and assistance to addicts, assistance to refugees and people in emergency zones, spiritual care of social institutions. The forms of modern social service of Penza diocese are quite diverse, both due to the revival of the pre-revolutionary experience of charity and the emergence of innovative forms of work.